Knowledge, Awareness, and Perceptions of Cervical Cancer and Screening Among Women in Rural South India - Eric Kwasi Elliaso; Atul Khajuria; Stephen Monday; J. Samuel Kamanda (International Journal of Oncological Nursing and Practices, 2025)
Background: Cervical cancer is still a major public health problem in South India, with rising figures of morbidity and mortality, in spite of progress in prevention, early detection, and treatment. Cervical cancer is the second leading cause of death due to cancer among Indian women, with around 123000 new cases and 67000 deaths every year. The delay in diagnosing CVD and low participation in screening programs is due to poor awareness of CVD in rural areas of South India, along with limited access to health care and some socio-cultural factors. Methods: This study employed a cross-sectional survey design to assess the knowledge, awareness, and perceptions of cervical cancer and its screening among women in rural South India. A total of 1,200 women aged 18 to 65 years were selected through stratified random sampling from both urban and rural areas. Data were collected using structured interviews and focus group discussions (FGDs), analyzing quantitative data with SPSS Statistics and qualitative data using thematic analysis. Results: 45% of women had heard of cervical cancer, but knowledge of risk factors and symptoms was low; only 35% were aware that HPV was a risk factor. Only 22% of participants were aware of screening methods like Pap smears, and just 15% of the HPV vaccine. The most common barriers to screening were lack of awareness (50%), financial constraints (45%), and cultural stigma (30%). Higher education and income were associated with better knowledge of cervical cancer and higher participation in screening. Moreover, cultural beliefs and myths, such as linking cervical cancer to shame and immorality, contributed greatly to the reluctance of women to seek medical treatment. Conclusion: Cervical cancer is one of the leading causes of cancer deaths among women in rural South India, thus highlighting the need for increasing awareness amongst women in these rural settings. The identified barriers, such as cultural stigma, economic barriers, and misperception, lead to late diagnosis and low commitment to the screening program. Addressing the burden of cervical cancer, particularly in rural areas, relies upon continuing to improve health literacy, expanding access to screening, and overcoming the cultural stigma associated with the disease. Community awareness through educational programs and affordable screening facilities needs to be enhanced for early detection and prevention.
Keywords: Awareness; HPV vaccine; Stigma; barriers to healthcare; cervical cancer; health education; rural south India; screening